Large pore ordered mesoporous silica materials with 3D cubic Ia3d structure. A comprehensive gas adsorption study. - Thommes, Matthias; et al. (Studies in Surface Science and Catalysis, 2007)
The paper deals with the systematic gas adsorption investigation and structural characterization of novel ordered mesoporous SiO2 materials with 3D cubic Ia3d structure (KIT-6). The pore condensation and hysteresis behavior of nitrogen (at 77.4 K) and argon (at 77.4 K and 87.3 K) was studied in KIT-6 silicas of different porosities and various mean pore diams. (from 5 nm up to 11 nm). We compared the sorption and phase behavior of nitrogen and argon confined to these 3-D cubic porous systems with their behavior in pseudo 1-D pore systems (e.g. SBA-15). Our results provide information on how pore connectivity and network effects influence pore condensation and hysteresis, and the validity of the single pore model for the pore size anal. of materials consisting in pore networks is discussed. [on SciFinder(R)]
Keywords: mesoporous silica porosity nitrogen argon adsorption